Kinetics from castor oil extraction using ethanol as solvent - Boligon, Suzana Diel; Scher, Ana Carolina; Wenzel, Bruno München (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
The sensitization for energy issues and environmental resulting from burning fossil fuels encourage the search for materials, inputs and renewable sources of energy. The biofuel is one of these renewable sources and is produced from vegetable oils extracted from raw material such as castor (Ricinus communis). It has been investigated as a raw material due to the high oil content in the seed, the possibility of plantations in regions with water deficit and high agricultural productivity. In front of the possibility of developing a simplified process for the production of biodiesel, such as in situ transesterification, which avoids the previous separation of the oil existing in the micelle, the present work aims to evaluate the kinetic behavior of extraction from castor oil using ethanol as solvent. In this context, experimental data were obtained about the kinetic from castor oil using ethanol in several conditions of temperature, as well as, fitting mathematical models able to describe the kinetic of the system castor-oil-ethanol. The castor seed used in the work were characterized about its humidity, oil content and acidity, having been obtained 4.86 %, 43.3 % and 2.1 %, respectively. The experiments were carried out in batch using sealed Erlenmeyer flasks in a thermostatic bath with reciprocal agitation to investigate the extraction process at different temperatures (25, 35 and 45 ºC) and solid-liquid ratio equal to 0.08 (g/ml). The percentage extractions were quantified in times of 15, 30, 45, 60, 120, 180, 240, 300, 480, 600 and 1440 min. For description of kinetics extraction, the fit of three different kinetic models to the experimental data was tested, pseudo-first order (PFO), pseudo-second order (PSO) and Patricelli. From the calculation of the corrected Akaike information criterion (AICc), the PSO model was the one that best described the extraction kinetics. In this way, the results obtained in this work contribute to expand the knowledge about the extraction process of castor oil with ethanol as solvent.